In situ study of phase transformations during laser-beam welding of a TiAl alloy for grain refinement and mechanical property optimization. (July 2015) - Liu, Jie; Staron, Peter; Riekehr, Stefan; Stark, Andreas; Schell, Norbert; Huber, Norbert; Schreyer, Andreas; Müller, Martin; Kashaev, Nikolai
Abstract: In situ time-resolved X-ray diffraction by synchrotron radiation was used to monitor the phase transformations and grain-refining processes during laser-beam welding of a γ-TiAl-based alloy. The heating rate plays an important role of grain refinement. A high heating rate suppresses solid–solid phase transformations. The superheated γ grains serve as heterogeneous nuclei for β grains on subsequent solidification and refine the lamellar colonies. At low heating rate, diffusion-based transformations are observed on heating and coarse lamellae are formed after welding. The refined lamellar colonies improve the mechanical properties. Highlights: At high heating rate, the material disintegrates directly into the liquid phase. High heating rate generates superheated γ, serving as nucleation sites for β grains. Lamellae colonies are refined and mechanical properties are improved by fast heating. Low heating rate leads to phase transformation and no visible superheated γ.